Proclaiming Colonial Urban Heritage: Towards an Inclusive Heritage-interpretation for Colombo’s Past - Harsha Munasinghe (Journal of Contemporary Urban Affairs, 2022)
Colombo, Sri Lanka’s commercial capital is a forceful creation of European colonialists who occupied the island for over four centuries. Its urban structure displays the social fragmentation sought by the rulers. Colombo elaborates an extraordinary process of city-making, stratified with its Dutch-origin, British-reshaping, and post-colonial adaptation. Proclaiming such a contested past as an inheritance requires an inclusive heritage interpretation. The recent renovation of monumental buildings for potential market values and demolishing minor architecture do not display such a heritage interpretation. This, placing undue attention on a selected social group, is found to be further emptying the compartmentalized city. The exclusion of some sub-societies also cost possible stewardship to urban heritage. Having observed the non-sustainability of current heritage-interpretation practised in Colombo, we searched for alternative means to unify societies in time-space thus sustaining the diversity of urban spaces. Our empirical studies have established the need to integrate the inherent cultural values of the colonial-built urban fabric in heritage interpretation. The results of vibrant heritage-interpretation results have been studied through a literature survey with aims to contribute towards the development of an inclusive heritage interpretation practice to protect Colombo’s colonial past sustainably.